Liberal culturalism and the individual: an alternative account of cultural identities - Daşhan, Fulya Özlem. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
In my thesis I aim to provide a philosophical basis to argue for a version of Pluralism which gives theoretical support for a form of Political Liberalism that is oriented towards enhancing communication among a diversity of cultures at the utmost level. I argue that the basic commitments of Political Liberalism to egalitarianism and to the autonomy of the individuals presuppose that the state be a pluralist one in which a diversity of cultures function to be the context of choice for the individuals.In order to argue for the philosophical position of Pluralism that I adopt at the end of my thesis I introduced an alternative account of autonomy. In this new account, an individual's autonomy no longer amounts to a rather obscure activity of "willing to will", but to one's capacity to choose instead. In this respect I have been able to show that an individual's autonomy diminishes if his scope of choices is diminished. That enabled me to argue that the widest scope of choices can only be maintained in line with Pluralism. The alternative account of autonomy and the anti-essentialist understanding of cultural identities that I have provided so far has enabled me to conclude that diversity of cultures is the context of choice for an individual. In this respect Pluralism is the most appropriate philosophical position that is compatible with the alternative account of the autonomous individual.
Keywords: Liberalism.; Multiculturalism.